2011
DOI: 10.1007/s10844-011-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

Message classification as a basis for studying command and control communications—an evaluation of machine learning approaches

Abstract: Specifically, we report the results from evaluating machine leaning with respect to two metrics of classification performance: (1) the precision of finding a known transition between two activities in a work process, and (2) the precision of classifying messages similarly to human researchers that search for critical episodes in a workflow.The results indicate that classification based on text only provides higher precision results with respect to both metrics when compared to other machine learning approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The annotation schema creates a set of distinct objects of study in the form of a set of episodes, which in turn direct further analysis by making video logs or observer reports at specific points in time relevant to study. The four stages of Rosell and Velupillai could similarly be described as re-formulations of the stages in qualitative data analysis introduced by Miles. Due to the similarities between the paradigm of data mining research and data analysis in decision making research, we had previously conducted a study on using data mining methods in text analysis (Leifler and Eriksson, 2010b). In our evaluations, we found that of all the metadata found in communications between members of a group of decision makers, the message texts were the most significant factors when attempting to emulate human classifications by machine classification.…”
Section: Data Analysis Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The annotation schema creates a set of distinct objects of study in the form of a set of episodes, which in turn direct further analysis by making video logs or observer reports at specific points in time relevant to study. The four stages of Rosell and Velupillai could similarly be described as re-formulations of the stages in qualitative data analysis introduced by Miles. Due to the similarities between the paradigm of data mining research and data analysis in decision making research, we had previously conducted a study on using data mining methods in text analysis (Leifler and Eriksson, 2010b). In our evaluations, we found that of all the metadata found in communications between members of a group of decision makers, the message texts were the most significant factors when attempting to emulate human classifications by machine classification.…”
Section: Data Analysis Methodsmentioning
confidence: 97%
“…Thus, using text-based classification of messages was considered an viable option for filtering the datasets used in analysis. Based on earlier work on the feasibility of using automatic pattern extraction in texts for supporting data exploration (Leifler and Eriksson, 2010b), and design criteria elicited from interviews with researchers in command and control (Leifler and Eriksson, 2010a), we designed a prototype tool to create patterns from texts. 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the similarities between these two paradigms, we had previously evaluated the technical soundness of using data mining methods in text analysis (Leifler and Eriksson, 2010) to support the exploration of patterns. We argue that, as the work process described by the ESDA model coincides well with the scatter/gather paradigm of how data mining tools are to be used, tools for data mining could probably fit the tasks in ESDA well.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…In our previous study on classification of messages and observer reports from decision-making scenarios, we found text clustering in particular to be useful as a pattern extraction technique (Leifler and Eriksson, 2010). Text clustering can be used to relate texts to one another based on distance metrics.…”
Section: Pattern Extractionmentioning
confidence: 99%